Case Report: Daratumumab in a Patient With Severe Refractory Anti-NMDA Receptor Encephalitis - Ratuszny, Dominica; Skripuletz, Thomas; Wegner, Florian; Groß, Matthias; Falk, Christine; Jacobs, Roland; Ruschulte, Heiner; Stangel, Martin; Sühs, Kurt-Wolfram (Frontiers in Neurology, 2020)
Anti-NMDA receptor encephalitis is the most common type of antibody mediated autoimmune encephalitis (AIE). Patients often develop neuropsychiatric symptoms and seizures, women are affected about for times more than men, and in about 50% the disease is associated with a neoplasia, especially teratomas of the ovary. We describe the case of a 20-year-old woman, suffering from a severe therapy refractory course of anti-NMDA receptor encephalitis. Treatment included glucocorticoids, plasma exchange, intravenous immunoglobulins, rituximab and bortezomib without clinical improvement. She spent about 200 days on intensive care unit followed by several weeks on intermediate care unit. The continuous observation period was about 9 months, with close follow ups every 4 -6 weeks afterwards. As this disease is potentially life threatening and can lead to irreversible brain atrophy, development of further therapy strategies are of great importance. Our case describes a successful treatment for therapy refractory anti-NMDA receptor encephalitis using the anti-CD38 antibody daratumumab.